AKTIVITAS BELAJAR SISWA PADA MATERI STUKTUR ATOM KELAS X MIA SEKOLAH MENENGAH ATAS NEGERI 4 PONTIANAK - Lesi Weni Sari; Cawang Cawang; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACT This research is motivated by the low student activity, which affects learning outcomes. The aims of this research were to describe and determine students activity on atomic structure lesson during chemistry teaching process. About 36 students of class X MIA 5 was choseen as samples in this research using purposive sampling method. The students activity data were collected through observations, questionnaires and interviews, using validated instruments. The results showed that the highest aspect of student activity was emotional activity (76,85%), and then declined gradually to listening activity(74,65%), visual activity (67,36%), writing activity (61,46%), and oral activity (38,42%). Emotional activity showed the highest score since students were eager to study chemistry subject, especially atomic structure lesson mean while oral activity was the lowest activity since the students were not confident to ask questions and express opinions.Keywords: Students’ learning activity, atomic structure